2018
DOI: 10.1136/annrheumdis-2017-212662
|View full text |Cite
|
Sign up to set email alerts
|

EULAR recommendations for the health professional’s approach to pain management in inflammatory arthritis and osteoarthritis

Abstract: Pain is the predominant symptom for people with inflammatory arthritis (IA) and osteoarthritis (OA) mandating the development of evidence-based recommendations for the health professional's approach to pain management. A multidisciplinary task force including professionals and patient representatives conducted a systematic literature review of systematic reviews to evaluate evidence regarding effects on pain of multiple treatment modalities. Overarching principles and recommendations regarding assessment and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
0
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(252 citation statements)
references
References 76 publications
5
196
0
18
Order By: Relevance
“…In contrast, a 2017 meta-analysis from a EULAR Taskforce conducted specifically in people with RMDs suggested that exercise associated with more uniformly positive effects on pain management [6], which is a positive finding and specific to RMDs. As such, because pain has great within-person variability, not only within a day but also between days [17], perhaps engaging people with RMDs in exercise at times when pain is experienced less, should be considered as an option prior to giving pain-relief medication in order to engage in exercise.…”
Section: Exercise May Potentially Reduce Pain As An Intervention In Imentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, a 2017 meta-analysis from a EULAR Taskforce conducted specifically in people with RMDs suggested that exercise associated with more uniformly positive effects on pain management [6], which is a positive finding and specific to RMDs. As such, because pain has great within-person variability, not only within a day but also between days [17], perhaps engaging people with RMDs in exercise at times when pain is experienced less, should be considered as an option prior to giving pain-relief medication in order to engage in exercise.…”
Section: Exercise May Potentially Reduce Pain As An Intervention In Imentioning
confidence: 96%
“…Even in healthy adults, the usual recommended dose of 4 g/d of acetaminophen may associate with elevated aminotransferases [24]. The most recent EULAR recommendations for managing pain in rheumatic conditions suggest usage of paracetamol, topical NSAIDs and capsaicin as first-line treatments, with the potential side-effects of NSAIDs to be taken into account when prescribing such agents [6].…”
Section: Increasing Pain Relief Medication May Have Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…They recommended physical activity/exercise regimes and diet/weight management to help manage RA pain [59]. The effects of physical activity and exercise are increasingly being characterized in a number of pain models [62,136,146,154], but not yet RA-associated pain.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…A média dos valores para os desfechos medidos nos dos períodos para cada grupo estão apresentados na tabela 3. Infelizmente não existem estudos com o uso do vídeo game em pacientes com OA de joelho para comparação dos resultados, mas um dos pontos principais para a melhora geral observada da dor, força muscular e função dos pacientes tratados é que o programa de fisioterapia proposto englobou as técnicas e recursos com melhores resultados propostos pelos guidelines atuais (Brosseau et al, 2011;Brosseau et al, 2017;Geenen et al 2018).…”
Section: Tabela 1-características Da Amostraunclassified